1986
DOI: 10.1161/01.cir.73.3.444
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary papaverine: an ideal coronary vasodilator for studies of the coronary circulation in conscious humans.

Abstract: An ideal coronary vasodilator for studying coronary flow reserve in humans would rapidly produce maximal coronary vasodilation, be short acting to permit repeated measurements, and not alter systemic hemodynamics. The two commonly used vasodilators (dipyridamole and meglumine diatrizoate) do not satisfy these criteria; meglumine diatrizoate does not produce maximal hyperemia and dipyridamole has a long duration of effect (greater than 30 min). In this study we used a subselective coronary Doppler catheter to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(120 citation statements)
references
References 29 publications
1
118
0
1
Order By: Relevance
“…20 The coronary flow reserve was normal in all control subjects and in eight HTN patients and was slightly reduced in two HTN patients. However, the mean value of coronary flow reserve was significantly lower in HTN patients than in normotensive subjects (P<.05) (Table).…”
Section: Coronary Blood Flow Studymentioning
confidence: 82%
See 1 more Smart Citation
“…20 The coronary flow reserve was normal in all control subjects and in eight HTN patients and was slightly reduced in two HTN patients. However, the mean value of coronary flow reserve was significantly lower in HTN patients than in normotensive subjects (P<.05) (Table).…”
Section: Coronary Blood Flow Studymentioning
confidence: 82%
“…Coronary flow reserve was calculated as the ratio of peak blood flow velocity (maximal kilohertz shift after papaverine) to resting blood flow velocity (average of two successive measures, the second of which was performed after return to baseline coronary flow velocity). 20 …”
Section: Catheterization Protocolmentioning
confidence: 99%
“…Hyperosmolar ionic contrast media do not produce maximal vasodilation. 10 The exact dose of intracoronary papaverine that is needed to induce maximal coronary vasodilation has recently been established. Wilson and White'0 compared the coronary hyperemic response after 4, 8, 12, and 16 mg intracoronary papaverine and reported a maximal hyperemic response after 8 or 12 mg in all coronary arteries.…”
Section: Resultsmentioning
confidence: 99%
“…Invasive studies have shown that when maximal coronary dilatation is induced, blood flow or blood flow velocity increases more in normal vessels than in those affected by significant stenosis. [17][18][19] Measurement of blood flow after the use of coronary vasodilators would allow noninvasive assessment of flow reserve in the LIMA and may be useful in the assessment of graft stenoses of moderate severity. This technique has been reported in the assessment of LAD stenoses using transesophageal echocardiography.…”
Section: Discussionmentioning
confidence: 99%